HUKUM PELAKSANAAN SINDIKASI DENGAN LEMBAGA KEUANGAN KONVENSIONAL - Nurfitriani, Nurfitriani (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
The implementation of a syndicated contract between Islamic financial institutions and conventional financial institutions according to National Sharia Council – Indonesian Ulama Council (DSN-MUI) is permitted under one condition that the documents are arranged in such a way in order to avoid administrative mixture between the halal and the ribawi. Using a separated account for the two parties; make one document for Islamic financial institution and so does for conventional financial institutions, separately. In contrast to syndication by fellow Islamic financial institutions where the accounts of contract documents and other documents can be arranged in one document.